Market Contestability and Bribe Solicitations: Evidence Across Stages of Firms' Operations - Rajeev K. Goel; Ummad Mazhar; James W. Saunoris (Center for Economic Studies and ifo Institute (CESifo), 2018)
Adding to the literature on factors driving corruption and bribery, this paper examines the effect of contestability in business operations on bribe solicitations. Contestability undermines bureaucratic rent-seeking potential and this paper tries to capture this empirically using cross-country survey data. Results show that the relatively greater contestability of business startup procedures compared to startup regulatory times led to fewer bribe demands; however, property registration regulations with lower relative contestability led to more bribe demands, especially for import licenses. Finally, older and larger firms received lower bribe demands, ceteris paribus.
Keywords: K42; D73; M21; 330; bribery; corruption; contestability; import licenses; operating licenses; regulation